Sentencing and the over-representation of people with cognitive disability in the Australian criminal justice system - Henderson, Calum A. F.; Bull, Melissa (Current issues in criminal justice, 2024)
People with Cognitive Disability (PWCD) are over-represented in Australian and International Criminal Justice Systems (CJS). Research has focused on the disadvantages experienced by PWCD which bring them into earlier and more continuous contact with the CJS than the general population. There has been little empirical analysis of how sentencing might contribute to overrepresentation. This article reports on a project which investigated: (1) the characteristics of PWCD who appeared before Queensland courts to be sentenced; and (2) the factors that judges considered during the sentencing of PWCD. An inductive thematic analysis of 34 sentencing remarks transcripts from Queensland's Supreme and District Courts provided a descriptive overview to address the first component. Themes addressing the second component included: difficulties and disadvantages; capabilities; and the subjectivities of defendants. Interpreted using critical sociological perspectives on punishment, these themes demonstrated how judges navigated a tension between responding to defendants' needs and protecting the community from a 'dangerous other'. The community was often prioritised, contributing to the enmeshment of PWCD in the CJS. This adds to over-representation and raises the dilemma of how to respond to community safety concerns while meeting the potentially complex needs of PWCD without drawing them more deeply into the CJS.